Penatalaksanaan pada Nn. I Usia 21 Tahun dengan Demam Dengue Melalui Pendekatan Kedokteran Keluarga di Puskesmas Kedaton Bandar Lampung - Winata, Afriza; Angraini, Dian Isti (CV. Jasa Sukses Abadi, 2024)
Dengue fever (DF) is an acute viral infectious disease caused by the dengue virus which in general can be characterized by symptoms of fever for 2-7 days, accompanied by other symptoms in the form of bleeding, such as nosebleeds and red spots on the body (ptekiae), bleeding gums, decreased platelets, the form of hemoconcentration in the form of plasma leakage with signs such as increased hematocrit, ascites, pleural effusion. The purpose of this case report is to Implementing family doctor services by identifying risk factors, clinical problems, and patient management based on Evidence-Based Medicine that is family-approach, patient-centred and community-oriented. The study conducted is a case report. Primary data were obtained through history taking, physical examination and home visits. Secondary data were obtained from the patient's medical records at the puskesmas. Assessment is carried out based on a holistic diagnosis from the beginning, process, and end of the study quantitatively and qualitatively. Patient is female with complaints of fever since 4 days ago. Fever followed by weakness, hedache, and nausea. In this case, the diagnosis and treatment have been carried out according to the latest theory and journals. After the intervention, there was an improvement in patient symptoms and an increase of patient knowledge.